PEMBUATAN BATU BATA RINGAN DARI SAMPAH PLASTIK DAN CAMPURAN FLY-ASH SEBAGAI BENTUK PENGELOLAAN SAMPAH DI DESA WISATA BONJERUK - Anang Fakhrrurahman; Kumala, Malya; Rosalia, Lutfiah Ayu; Siptiani, Eka; Ambarwati, Zaskia Putri; Hamsy, Lalang Setiawan; Setiawan, Yahya; Sari, Mauliya Alina; Jannah, Rafaatul; Misrohatun, Misrohatun; Mahendra, Yusril Iza; Ngudiyono, Ngudiyono (Universitas Mataram, 2025)
The Community Service Program (KKN) of Mataram University in Bonjeruk Village aims to address the issue of plastic waste management by educating the community on utilizing waste into economically valuable products. One of the proposed solutions is training in the production of lightweight bricks made from plastic waste mixed with fly ash from the Jeranjang Steam Power Plant (PLTU Jeranjang). The activities are carried out through a participatory approach, involving the community in various stages, including an initial survey, socialization, training, mentoring, as well as documentation and publication. The brick-making process includes burning plastic waste, mixing it with fly ash and used oil, molding, cooling, and drying before it is ready for use. The results of this program indicate that processing plastic waste into lightweight bricks can be an innovative and sustainable solution for reducing waste while also providing economic opportunities for the people of Bonjeruk Village.